SPAK Sensitive Regulation of the Epithelial Na+ Channel ENaC - Musaab Ahmed; Madhuri S. Salker; Bernat Elvira; Anja T. Umbach; Hajar Fakhri; Amal M. Saeed; Ekaterina Shumilina; Zohreh Hosseinzadeh; Florian Lang (Karger Publishers, 2015)
Background/Aims: The WNK-dependent STE20/SPS1-related proline/alanine-rich kinase SPAK participates in the regulation of NaCl and Na+,K+,2Cl- cotransport and thus renal salt excretion. The present study explored whether SPAK has similarly the potential to regulate the epithelial Na+ channel (ENaC). Methods: ENaC was expressed in Xenopus oocytes with or without additional expression of wild type SPAK, constitutively active T233ESPAK, WNK insensitive T233ASPAK or catalytically inactive D212ASPAK, and ENaC activity estimated from amiloride (50 µM) sensitive current (Iamil) in dual electrode voltage clamp experiments. Moreover, Ussing chamber was employed to determine Iamil in colonic tissue from wild type mice (spakwt/wt) and from gene targeted mice carrying WNK insensitive SPAK (spaktg/tg). Results: Iamil was observed in ENaC-expressing oocytes, but not in water-injected oocytes. In ENaC expressing oocytes Iamil was significantly increased following coexpression of wild-type SPAK and T233ESPAK, but not following coexpression of T233ASPAK or D212ASPAK. Colonic Iamil was significantly higher in spakwt/wt than in spaktg/tg mice. Conclusion: SPAK has the potential to up-regulate ENaC.